2017
DOI: 10.1038/s41537-017-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to replicate genetic associations with schizophrenia in a cohort from north India

Abstract: Schizophrenia is a chronic, severe, heritable disorder. Genome-wide association studies, conducted predominantly among Caucasians, have indicated > 100 risk alleles, with most significant SNPs on chromosome 6. There is growing interest as to whether these risk alleles are relevant in other ethnic groups as well. Neither an Indian genome-wide association studies nor a systematic replication of GWAS findings from other populations are reported. Thus, we analyzed 32 SNPs, including those associated in the Caucasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…Study of a homogenous sample of Arab, Israeli families identified several single nucleotide polymorphisms in the 6q23.3 region that were associated with the disorder 7 . These associations were replicated in Icelandic 8 and large European samples 9 and were supported by findings in cohorts of German and Spanish 10 and North Indian patients 11 and by QTL analysis in independent European samples 12 . Studying Ahi1 expression levels in lymphoblasts from schizophrenia patients, we found reduced expression in patients with early onset of the disorder 13 , leading us to suggest that reduced Ahi1 levels may be associated with susceptibility to schizophrenia.…”
Section: Introductionsupporting
confidence: 65%
“…Study of a homogenous sample of Arab, Israeli families identified several single nucleotide polymorphisms in the 6q23.3 region that were associated with the disorder 7 . These associations were replicated in Icelandic 8 and large European samples 9 and were supported by findings in cohorts of German and Spanish 10 and North Indian patients 11 and by QTL analysis in independent European samples 12 . Studying Ahi1 expression levels in lymphoblasts from schizophrenia patients, we found reduced expression in patients with early onset of the disorder 13 , leading us to suggest that reduced Ahi1 levels may be associated with susceptibility to schizophrenia.…”
Section: Introductionsupporting
confidence: 65%
“…, Taylor et al 2016; Brant et al 2017; Park et al 2017), the total number of GWAS studies for AAs is still fairly low compared with populations of European ancestry (Peprah et al 2015) and replication of signals in AA populations is much less common (Marigorta and Navarro 2013). Moreover, the associations reported to be strong in Caucasians have been weaker (or even nonsignificant) in other ethnic groups (Gudbjartsson et al 2007; Omori et al 2008; Yamada et al 2009; Barnholtz-Sloan et al 2011; Tsai et al 2014; Prasad et al 2017) and some studies have reported effects with opposite sign in different populations (Lewis et al 2008; Yamada et al 2009). More recent studies have also confirmed the presence of genetic heterogeneity between ethnic groups for various traits (Brown et al 2016; de Vlaming et al 2017; Zhou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that an underlying genetic predisposition can affect both neurons and muscle cells. For example, AHI1 is associated with both schizophrenia and metabolic abnormalities of muscles 30,31 and perhaps could contribute to these two disease predispositions.…”
Section: Discussionmentioning
confidence: 99%